(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2015)
Stroke is the third most common cause of death in industrialized countries. Stroke is the most important cause of morbidity and longterm disability in Europe as well as in other industrialized nations. Prevalence rate was higher among men compared with women 3.44 and 2.41 per 1000 respectively. Data from the Northern Manhattan study showed the age adjusted incidence of first ischemic stroke per 100,000 was 88 in Whites 191 in Blacks and 149 in Hispanics. Black has almost thrice the risk of first ever stroke compared with Whites. The age adjustment stroke incidence rates for first ever stroke are 167 for White males, 138 for White females, 323 for Black males and 260 for Black females. Among American-Indian age 65-74, the annual rates per 1,000 population of new and recurrent stoke are 6.1 for men and 6.6 for women. Stroke accounted for about one of every 15 deaths in the United State in 2003. About 50 percent of these deaths occurred out of hospital. On average, about every three minutes someone dies of a stroke. In this review the modifiable and non-modifiable risks factors are discussed. J. Natl Inst. Neurosci Bangladesh 2015;1(1):22-26